The influence of principal leadership, school culture, and digital literacy on the performance of teachers at state vocational high schools in Rantau utara - Ragil Wahyuda Abrar; Marlina Siregar; Aziddin Harahap; Junita Junita; Muhammad Ardansyah (Lembaga Riset Mutiara Akbar, 2026)
This study aims to examine the influence of principal leadership, school culture, and digital literacy on teacher performance at state vocational high schools in Rantau Utara. A quantitative research approach was employed using path analysis to examine the relationships among the variables. The study involved 65 teachers selected through proportional random sampling. Data were collected using structured questionnaires and analyzed using descriptive statistics, assumption tests, simple correlation, and multiple correlation analyses with SPSS version 22.0. The findings reveal that principal leadership has a positive and significant influence on teacher performance (r = 0.535, p lower than 0.001), followed by digital literacy (r = 0.528, p lower than 0.001) and school culture (r = 0.416, p lower than 0.001). Simultaneously, principal leadership, school culture, and digital literacy explain 60.2% of the variance in teacher performance (R² = 0.602). These findings indicate that strengthening instructional leadership, fostering a positive school culture, and improving teachers' digital literacy are essential strategies for enhancing teacher performance. This study highlights the importance of integrating effective leadership, a supportive organizational culture, and digital competence to improve instructional quality and support the achievement of educational goals in vocational schools.